2008
DOI: 10.1063/1.2963492
|View full text |Cite
|
Sign up to set email alerts
|

Metallization contacts to nonpolar a-plane n-type GaN

Abstract: We have investigated the electrical characteristics of metallization contacts to nonpolar a-plane and polar c-plane n-type GaN. Pd Schottky diodes and x-ray photoemission spectroscopy measurements show that the Schottky barrier height of the a-plane GaN is lower than that of the c-plane GaN by 0.24 and 0.30eV, respectively. Ti∕Al Ohmic contacts to the a-plane n-GaN produce lower contact resistivity than that of the c-plane samples when annealed at 500°C. However, Ti∕Al contacts to the c-plane and a-plane GaN s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 14 publications
3
20
0
Order By: Relevance
“…Ag is the most commercially used reflector because of its high reflectivity and low contact resistance [11][12][13]. On the one hand, contacts to non-polar and semi-polar GaN produced poorer electrical characteristics than contacts to c-plane (0 0 0 1) samples [14][15][16]. In our previous work [17], we investigated the effect of different polarity on the electrical properties of Ag contacts to semi-polar p-GaN and showed that Ag contacts to (0 0 0 1) c-plane GaN became ohmic after annealing in air, whereas contacts to (1 1 À2 2) semi-polar GaN were non-ohmic.…”
Section: Introductionmentioning
confidence: 99%
“…Ag is the most commercially used reflector because of its high reflectivity and low contact resistance [11][12][13]. On the one hand, contacts to non-polar and semi-polar GaN produced poorer electrical characteristics than contacts to c-plane (0 0 0 1) samples [14][15][16]. In our previous work [17], we investigated the effect of different polarity on the electrical properties of Ag contacts to semi-polar p-GaN and showed that Ag contacts to (0 0 0 1) c-plane GaN became ohmic after annealing in air, whereas contacts to (1 1 À2 2) semi-polar GaN were non-ohmic.…”
Section: Introductionmentioning
confidence: 99%
“…These different behaviors could be explained as follows. For Ti/Al contacts to Ga-face n-GaN, annealing at temperatures above 700 C led to the formation of ohmic contacts, being attributed to the formation of AlN, generating N vacancies (donor defects) and two-dimensional electron gases (2DEG) at the AlN/GaN interface 6,12,19 and TiN phase, producing N vacancies. 20 The electrical degradation of Ti/Al contacts to N-face n-GaN at temperatures below 300 C was attributed to the generation of Ga vacancies near the n-GaN surface region caused by Ga outdiffusion.…”
Section: Resultsmentioning
confidence: 99%
“…For Ti/Al contacts to Ga-face n-GaN, the annealing-induced improvement was attributed to the generation of donorlike N vacancies and 2DEG. 6,11,25 For N-face n-contacts, the annealing-induced degradation was attributed to the absence of polarization-induced 2DEG. 11 These mechanisms are based on the presence of interfacial AlN formed as a result of annealing at temperatures above 400°C.…”
Section: H276mentioning
confidence: 97%